Digitalization Music Ecosystem As an Impact of COVID-19 in Medan - Suci Maulidya (TALENTA Publisher, 2026)
This study examines the digitalization of the music ecosystem as an impact of the COVID-19 pandemic in Medan. The research aims to identify the transformation of music production, distribution, and consumption from analog systems to digital practices within local music communities. In addition, it analyzes the role of digital platforms and music aggregators in shaping new patterns within the music industry in North Sumatra. The research employs a library research method, utilizing secondary data sources such as academic journals, books, media articles, and statistical reports. The findings indicate that, in the aspect of music production, there has been a significant shift from conventional systems to technology-based digital production. The emergence of home recording practices and the use of Digital Audio Workstations (DAWs) have enabled musicians to independently produce music at relatively lower costs, thereby increasing the number of independent musicians and expanding access to music creation. In terms of distribution, digital platforms such as YouTube, Spotify, and other streaming services have become the primary channels for disseminating musical works. Furthermore, the presence of digital platforms and music aggregators has facilitated artists— particularly musicians and composers—in distributing their works more efficiently. This transformation reflects a broader cultural shift toward modernization, where digital publication and independent production practices have become essential, ultimately providing greater creative freedom for musicians to produce and distribute their own works.